2018
DOI: 10.3390/fluids3010011
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Mixed Convection in Ventilated Cavities with Different Aspect Ratios

Abstract: An unsteady numerical investigation on mixed convection in a two dimensional open ended cavity with different aspect ratios is carried out. In this investigation, uniform temperature is set to the left and the right sides of the cavity while the other surfaces are adiabatic. The simulation is performed for a wide range of Reynolds numbers (Re = 100-1000) and Richardson numbers (Ri = 0.132-6.5 × 10 2 ), and various cavity aspect ratios (L/D = 0.5-4.0) and H/D = 0.1. Governing equations are solved using a cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Over the decades, the research on mixed convective stream and thermal energy transference in channel cavities are of fundamental interest in applied science research because of its applications in several fields [1][2][3][4][5][6][7][8][9][10]. Manca et al [11] discovered the influence of the location of a hot wall on the combined convective flow of an open cavity that exists in a channel.…”
Section: Introductionmentioning
confidence: 99%
“…Over the decades, the research on mixed convective stream and thermal energy transference in channel cavities are of fundamental interest in applied science research because of its applications in several fields [1][2][3][4][5][6][7][8][9][10]. Manca et al [11] discovered the influence of the location of a hot wall on the combined convective flow of an open cavity that exists in a channel.…”
Section: Introductionmentioning
confidence: 99%
“…It was also noted that the average Nusselt number and Poiseuille number increases by increasing the Hartman number. Carozza [21] performed a numerical investigation on mixed convection in a two dimensional open ended cavity with different aspect ratios and focused that the enhancement of heat transfer rate depends on the increasing Re and the assisting configuration. Devera and Hyhlik [22] conducted an experimental study to investigate the thermal field in a horizontal rectangular channel with two types of bottom boundary conditions and concluded that mass transfer causes stronger transient behavior above the bottom surface and enhancing of heat transfer, but the overall character of the thermal field remains the same as in case of heat transfer only.…”
Section: Introductionmentioning
confidence: 99%
“…They determined that an enhancement of heat transfer in presence of baffle. Finally, an unsteady numerical investigation on mixed convection in a two dimensional open ended cavity with different aspect ratios was presented by [9]. In his investigation, an uniform temperature is set to the left and the right sides of the cavity while the other surfaces are adiabatic.…”
Section: Introductionmentioning
confidence: 99%